Le respect de la nature et l’art dans les rites amérindiens d’après quelques essais de J.M.G. Le Clézio - Nielipowicz, Natalia (Romanica Silesiana)
J.M.G. Le Clézio’s passion for Amerindians, closely reflecting his interest in mysticism, is expressed in many of his texts: essays, translations and fictional texts. Their culture is often contrasted with materialism, characteristic of the culture of the Western civilization. This opposition relates to all areas of life and especially to the relation of man to the earth, which can be seen, among others, in the process of creating art. The indigenous art of American Indians, natural and associated with rituals, becomes a magical practice, holy and haunted by ghosts. Through analysing his essays, the article attemps to answer the question of the relationship that Le Clézio sees in the Amerindian’s respect for the forces of nature and the artistic expression: drawing, painting, singing and ritualistic dancing. It also considers the consequences of the presence of nature in the world of American Indian rituals. Key words: rituals, art, Amerindians, nature, holiness, faith